Antinociceptive profile of a synthetic curcuminoid derivative, 2,6-bis-4-(hydroxy-3-methoxy-benzilidine)-cyclohexanone in murine model of induced-nociception - Lee, Ming Tatt (2013)
Introduction: The present study investigated the antinociceptive potential of a synthetic curcuminoid derivative, 2,6-bis-4-(hydroxyl-3-methoxybenzilidine)- cyclohexanone, or BHMC in pain-induced models in mice. Problem statement: Pain is a major symptom of various diseases that persists to produce severe physical and psychological distress for many patients. However, current treatment for pain produced undesirable adverse effects thus limited their use. This has led to a search for new pharmacologically potent antinociceptive compounds with minimum or no adverse effects. Objective: The present study aimed to investigate the systemic, peripheral and supraspinal antinociceptive potential of BHMC in pain models in mice. The research project also aimed to further investigate the possible mechanism of action in systemic, peripheral and supraspinal antinociceptive effect of BHMC. Methodology: Systemic antinociceptive effect of BHMC was determined using acetic acid-induced abdominal constriction test,formalin induced-paw licking test and hotplate test. The systemic effect of BHMC was also evaluated via chronic constriction injury-induced neuropathic pain in mice. Peripheral and supraspinal antinociceptive effect of BHMC was evaluated via carrageenan-induced hyperalgesia test and thermal-induced nociception test,respectively. Results and discussion: It was demonstrated that systemic treatment of BHMC exhibited dose-dependent inhibitory effect in chemical- and thermalinduced nociception. Further investigation on the involvement of descending modulatory pathway in systemic antinociceptive effect of BHMC showed that BHMC selectively activated κ-opioid, A1-adenosine, D2-dopamine, Macetylcholine,GABAB, α2-noradrenaline and 5-HTA1 receptors. Activation of these inhibitory receptors triggered the efflux of potassium ion from nociceptive neuron,leading to neuronal hyperpolarisation. Hyperpolarisation of nociceptive neuron via nitric oxide (NO) independant cyclic guanosine monophosphate (cGMP) induced potassium (K+) channel opening was shown as one of the possible antinociceptive mechanism of systemic antinociceptive action of BHMC. Dose-dependant inhibitory effect of BHMC was also shown in CCI-induced hyperalgesia test in mice, which indicated a similar mechanism of action in BHMC-induced antinociception. It was also demonstrated that peripheral and supraspinal administration of BHMC produced dose-dependent antinociceptive effect, with peripheral antinociceptive effect of BHMC was via μ-,κ-opioid receptor and NOindependent cGMP/protein kinase G (PKG)/K+ channel activation; whereas supraspinal analgesic effect of BHMC was through κ-opioid/NO/cGMP/PKG/K+ channel activation. Conclusion: The present study demonstrated that BHMC possessed potential systemic, peripheral and supraspinal antinociceptive effect through mechanisms that caused the activation of K+ channels leading to neuronal membrane hyperpolarisation.